Pulsed laser synthesis of highly active Ag–Rh and Ag–Pt antenna–reactor-type plasmonic catalysts - Kane, Kenneth A.; Bertino, Massimo F. (Beilstein Journal of Nanotechnology, 2019)
Ag, Pt, and Rh monometallic colloids were produced via laser ablation. Separate Ag–Rh and Ag–Pt heterostructures were formed by mixing and resulted in groupings of Rh/Pt nanoparticles adsorbing to the concavities of the larger Ag nanostructures. The 400 nm Ag plasmonic absorption peak was slightly blue-shifted for Ag–Pt and red-shifted for Ag–Rh heterostructures. Catalytic activity for the reduction of 4-nitrophenol increased significantly for Ag–Pt and Ag–Rh compared to the monometallic constituents, and persisted at lower loading ratios and consecutive reduction cycles. The enhancement is attributed to the Rh and Pt nanoparticles forming antenna–reactor-type plasmonic catalysts with the Ag nanostructures.
Keywords: Ag; antenna–reactor; catalysis; heterostructures; laser ablation; multicomponent; nanoparticles; 4-nitrophenol; plasmonic; Pt; Rh

(untitled) - Halas, N. J.; Lal, S.; Chang, W.-S.; Link, S.; Nordlander, P. (Chem. Rev., 2011)

(untitled) - Jain, P. K.; Huang, X.; El-Sayed, I. H.; El-Sayed, M. A. (Acc. Chem. Res., 2008)

(untitled) - Dolinnyi, A. I. (J. Phys. Chem. C, 2015)

(untitled) - Carpin, L. B.; Bickford, L. R.; Agollah, G.; Yu, T.-K.; Schiff, R.; Li, Y.; Drezek, R. A. (Breast Cancer Res. Treat., 2011)

(untitled) - El-Sayed, I. H.; Huang, X.; El-Sayed, M. A. (Cancer Lett., 2006)

(untitled) - Hao, E.; Schatz, G. C. (J. Chem. Phys., 2004)

(untitled) - Linic, S.; Christopher, P.; Ingram, D. B. (Nat. Mater., 2011)

(untitled) - Evanoff, D. D.; Chumanov, G. (J. Phys. Chem. B, 2004)

(untitled) - Jain, P. K.; Lee, K. S.; El-Sayed, I. H.; El-Sayed, M. A. (J. Phys. Chem. B, 2006)

(untitled) - Bosbach, J.; Hendrich, C.; Stietz, F.; Vartanyan, T.; Träger, F. (Phys. Rev. Lett., 2002)

(untitled) - Manjavacas, A.; Liu, J. G.; Kulkarni, V.; Nordlander, P. (ACS Nano, 2014)

(untitled) - Atwater, H. A.; Polman, A. (Nat. Mater., 2010)

(untitled) - Christopher, P.; Xin, H.; Linic, S. (Nat. Chem., 2011)

(untitled) - Aslam, U.; Rao, V. G.; Chavez, S.; Linic, S. (Nat. Catal., 2018)

(untitled) - Boerigter, C.; Campana, R.; Morabito, M.; Linic, S. (Nat. Commun., 2016)

(untitled) - Zheng, Z.; Tachikawa, T.; Majima, T. (J. Am. Chem. Soc., 2014)

(untitled) - Wang, F.; Li, C.; Chen, H.; Jiang, R.; Sun, L.-D.; Li, Q.; Wang, J.; Yu, J. C.; Yan, C.-H. (J. Am. Chem. Soc., 2013)

(untitled) - Aslam, U.; Chavez, S.; Linic, S. (Nat. Nanotechnol., 2017)

(untitled) - Zhang, C.; Zhao, H.; Zhou, L.; Schlather, A. E.; Dong, L.; McClain, M. J.; Swearer, D. F.; Nordlander, P.; Halas, N. J. (Nano Lett., 2016)

(untitled) - Kane, K. A.; Reber, A. C.; Khanna, S. N.; Bertino, M. F. (Prog. Nat. Sci.: Mater. Int., 2018)

(untitled) - Roy, A.; Debnath, B.; Sahoo, R.; Chandrakumar, K. R. S.; Ray, C.; Jana, J.; Pal, T. (J. Phys. Chem. C, 2016)

(untitled) - Aditya, T.; Pal, A.; Pal, T. (Chem. Commun., 2015)